Mapping the Vineyard: Main Lines of Investigation Regarding the Parable of the Tenants in the Synoptics and Thomas - Lanier, Gregory R. (Currents in biblical research, 2016)
The Parable of the Tenants (Mk 12.1-12; Mt. 21.33-45; Lk. 20.9-19; GThom 65-66) is one of the most debated of all the parables ascribed to Jesus. Situated at the intersection of a host of important issues in Gospels scholarship—ranging from the synoptic problem, to the use of the OT in the NT, to the historical Jesus—it has generated a seemingly overwhelming quantity of secondary research in recent decades. This article aims to help orient scholars to the main areas of research on the parable, focusing specifically on six topics: narrative outline, formative influences (social-historical setting and intertextuality), source-critical hypotheses, symbolic/metaphorical correspondences of the narrative elements, authenticity and the ‘original’ version, and broad lines of interpretation. The conclusion offers reflections on what the substantial research on the parable can tell us about parable interpretation in general.